THE STUDY OF COMPARISON OF SINGLE-INCISION LAPAROSCOPIC VERSUS CONVENTIONAL LAPAROSCOPIC APPENDECTOMY: A COMPREHENSIVE SYSTEMATIC REVIEW - satrio Nugroho, Fredy; Rudy Budiantoro, Rudolf; Nur Alamsyah, Wahyu (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Acute appendicitis is highly prevalent in children with an acute abdomen, and appendectomy is still the main method of treatment for this disease. The standard treatments for acute appendicitis are early open surgery and laparoscopic surgery. The aim: The aim of this study to show about comparison of single incision laparoscopic versus conventional laparoscopic appendectomy. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Sciencedirect were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: Eight publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: HLA has a negative impact on quality of life and aesthetics because it requires three surgical incisions. On the contrary, in single-incision transumbilical laparoscopic appendicectomy (SILA), the incision is made around the umbilicus.